Karakteristik Sifat Kimia dan Organoleptik Churros Tersubtitusi Tepung Beras dengan Tepung Ubi, Chemical Characteristic and Organoleptic Churros Substituted with Rice Flour with Sweet Potato Flour - Mulidavi Mutya Rochmah; Anggun Desiana Sofa; Eva Elysa Oktaviys; Iffah Muflihati; Arief Rakhman Affandi (Jurnal Pangan dan Gizi, 2019)
This study aims to determine the effect of making churros from rice flour and sweet potato flour. This study uses a completely randomized factorial pattern with 2 factors, namely the comparison of the composition of rice flour and sweet potato flour. While the second factor is the type of flour used, namely purple sweet potato flour and Cilembu sweet potato flour. The resulting churros will be observed for quality including water content, fat content, and organoleptic test (preference and descriptive). The results of this study indicate that panelists prefer churros made of 30 TB: 70 TU. The lowest value of fat content is 30TB: 70TC which is 16,715%. Water content value of 30TB: 70TU with a value of 19.13%.